Fool or almighty?: readings on Machado de Assis and slavery - Campos, Raquel Machado Alves de (Revista de Letras, 2008)
Machado de Assis’s understanding of slavery and mainly of the abolitionist process is in the core of the readings which support a close linkage between Assis’s literary work and Brazilian society under the Second Reign. Such understanding is not, however, consensual among experts on the writer’s work. The issues dealt with in this paper concern the different visions of how Assis portrayed abolition and the slaves themselves, as well as the relation such visions bear with historiography of slavery in Imperial Brazil.